Respon Pertumbuhan Stek Tanaman Jeruk Lemon (Citrus Limon) terhadap Konsentrasi dan Lama Perendaman Zat Pengatur Tumbuh Sintetis - Refrian Adil Wijaya; Dewi Fithria; Dewi Junita; Hendri Sahputra (Universitas Teuku Umar, 2022)
The study used a Randomized Design Group (RAL) with 2 factors, the first factor being an organic ZPT(Z) with The standards are: Z0 (control), Z1 (150mg/l). ), Z2 (200mg/l), Z3 (250mg/l). ). Immersion time (P) with 3 levels namely P1 (2 hours), P2 (3 hours), P3 (4clock). There are 12 combinations of treatments that are repeated 3 times resulting in 36 experimental units. Experimental data is analyzed using variance analysis (ANOVA) and continued with real different tests (BNJ). The parameters observed in this study were: number of buds, height of buds, number of leaves, number of roots and length of roots. The results showed that the concentration of ZPT had a big effect on all parameters, because the length of immersion had a real effect on the parameters of the number of shoots and the length of the shoots, while on the parameters of the number of shoots and the length of the shoots. Shoots have a real effect, the leaves, the number of roots and the length of the roots have no real effect on all ages.Keywords: ZPT, Old Immersion, Lemon Cuttings Growth.